2016
DOI: 10.3389/fmicb.2016.00163
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Isotope Localization in Ammonia sp. (Foraminifera) of Oxygen-Depleted Environments: Results of Nitrate and Sulfate Labeling Experiments

Abstract: Some benthic foraminiferal species are reportedly capable of nitrate storage and denitrification, however, little is known about nitrate incorporation and subsequent utilization of nitrate within their cell. In this study, we investigated where and how much 15N or 34S were assimilated into foraminiferal cells or possible endobionts after incubation with isotopically labeled nitrate and sulfate in dysoxic or anoxic conditions. After 2 weeks of incubation, foraminiferal specimens were fixed and prepared for Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 54 publications
(80 reference statements)
7
54
1
Order By: Relevance
“…In a study of Ammonia sp. (phylotype T6) by Nomaki et al (2016), cells were observed to incorporate more 15 N-labeled nitrate and 34 S-labeled sulfate under dysoxic (in the study defined as O 2 = 0.1-22 μmol l − 1 ) than anoxic conditions, indicating the reduced activity of foraminifera in anoxic conditions. Additionally, LeKieffre et al (2017) have shown, using nanoSIMS analysis, that Ammonia sp.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In a study of Ammonia sp. (phylotype T6) by Nomaki et al (2016), cells were observed to incorporate more 15 N-labeled nitrate and 34 S-labeled sulfate under dysoxic (in the study defined as O 2 = 0.1-22 μmol l − 1 ) than anoxic conditions, indicating the reduced activity of foraminifera in anoxic conditions. Additionally, LeKieffre et al (2017) have shown, using nanoSIMS analysis, that Ammonia sp.…”
Section: Introductionmentioning
confidence: 77%
“…The morphology of the bacterial cells also differed between specimens of Ammonia sp. (phylotype T6) collected during different seasons from the same field site in Tokyo Bay (Nomaki et al, 2014(Nomaki et al, , 2016. The ultrastructural observations, therefore, suggest that during anoxic exposure, Ammonia spp.…”
Section: Potential Bacterial Endosymbionts In the Foraminiferal Cytosmentioning
confidence: 86%
See 3 more Smart Citations